Demonstration of Auxin Binding to Strawberry Fruit Membranes - Narayanan, Komaratchi R. (1981)
Presence of specific auxin-binding sites in strawberry fruit (Fragaria ananassa Duch. cv. Ozark Beauty) membranes has been demonstrated. These 1-naphthaleneacetic acid (NAA)-binding sites in the 80,000g to 120,000g fraction of the strawberry fruit membrane were pronase sensitive with an estimated equilibrium dissociation constant for NAA of 1.1 × 10(−6) molar. The minimum concentration of NAA required to stimulate strawberry fruit growth was at least one order of magnitude higher than the minimum concentration of NAA required to stimulate corn coleoptile elongation. This was consistent with the higher equilibrium dissociation constant (lower affinity) for auxin binding to strawberry fruit membranes than to corn coleoptiles. Twelve auxin analogs, ranging from very strong to weak auxins, were tested for abilities to stimulate in situ strawberry fruit growth and to bind (displace or compete with NAA) to strawberry fruit membranes. The observed positive correlation (r = 0.74) between the in vitro binding to the 80,000 to 120,000 membrane fraction and the in situ biological activity of these analogs indicated that the NAA-binding sites in strawberry fruit membranes may represent physiologically relevant auxin receptors.